1975
DOI: 10.1002/jsfa.2740260212
|View full text |Cite
|
Sign up to set email alerts
|

A seaweed residue unsuitable as a major source of energy or nitrogen for growing Pigs

Abstract: When fed at the level of 50 P;; of the diet, the dried residue of Ascophyllum nodosum, remaining after alginate extraction, was found to cause diarrhoea in pigs within 7 days. Digestibility coefficients for a diet containing 50% seaweed residue, 20% barley, 19 % wheat and 10% fish meal were 0.47 for energy and 0.52 for nitrogen. By difference calculation the digestible energy and digestible crude protein values of the seaweed residue were determined to be 2.2 MJ and -30 g/kg dry matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Supplementation of Mg and S is not commonly required for monogastric diets, but may be valuable in diets for grazing ruminants in tropical regions (Machado et al 2015). Considering the high osmotic capacity of specific minerals, the use of this U. lactuca sample would increase the risk of low faecal consistency, diarrhoea and wet droppings in pigs and poultry as shown for high inclusion of an Ascophyllum nodosum residue in pigs (Whittemore and Percival 1975). In addition, interaction between minerals and trace elements may reduce the absorption of specific nutrients from the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of Mg and S is not commonly required for monogastric diets, but may be valuable in diets for grazing ruminants in tropical regions (Machado et al 2015). Considering the high osmotic capacity of specific minerals, the use of this U. lactuca sample would increase the risk of low faecal consistency, diarrhoea and wet droppings in pigs and poultry as shown for high inclusion of an Ascophyllum nodosum residue in pigs (Whittemore and Percival 1975). In addition, interaction between minerals and trace elements may reduce the absorption of specific nutrients from the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…recorded weight loss in pigs fed 100 g kg −1 of a meal produced from A. nodosum , an alga that characteristically contains less than 100 g kg −1 of protein in the DM. Similarly, Whittemore and Percival concluded that the residue from A. nodosum after extraction of alginate was poorly digested and unsuitable as a protein and energy source for pigs. There are few published reports on the inclusion of brown macroalgae in formulated compound feed for fish.…”
Section: Effects On Growth Performance Protein Utilization and Carcamentioning
confidence: 99%
“…This could be explained partially by a possible increased metabolic fecal nitrogen loss in association with a zero utllization of the kelp nitrogen, which is strongly bound to cellulose (Whyte and Englar 1975b Whittemore and Percival (1975) The value of kelp as a stimulator of feed intake has been documented. Morris (1932) showed increases of up to 30% in food consumption and an 87o increase in the growth of rats fed a high protein diet with 6Vo added Macrocystis pyrifera meal.…”
Section: Resultsmentioning
confidence: 99%